Functional identification of purine permeases reveals their roles in caffeine transport in tea plants (Camellia sinensis) - Zhang, Yazhen; Wei, Kang; Guo, Lingling; Lei, Yuping; Cheng, Hao; Chen, Changsong; Wang, Liyuan (Frontiers in Plant Science, 2022)
Caffeine is a characteristic secondary metabolite in tea plants. It confers tea beverage with unique flavor and excitation effect on human body. The pathway of caffeine biosynthesis has been generally established, but the mechanism of caffeine transport remains unclear. Here, eight members of purine permeases (PUPs) were identified in tea plants. They had diverse expression patterns in different tissues, suggesting their broad roles in caffeine metabolism. In this study, F1 strains of "Longjing43" ♂ × "Baihaozao" ♀ and different tea cultivars were used as materials to explore the correlation between caffeine content and gene expression. The heterologous expression systems of yeast and Arabidopsis were applied to explore the function of CsPUPs. Correlation analysis showed that the expressions of CsPUP1, CsPUP3.1, and CsPUP10.1 were significantly negatively correlated with caffeine content in tea leaves of eight strains and six cultivars. Furthermore, subcellular localization revealed that the three CsPUPs were not only located in plasma membrane but also widely distributed as circular organelles in cells. Functional complementation assays in yeast showed that the three CsPUPs could partly or completely rescue the defective function of fcy2 mutant in caffeine transport. Among them, transgenic yeast of CsPUP10.1 exhibited the strongest transport capacity for caffeine. Consistent phenotypes and functions were further identified in the CsPUP10.1-over-expression Arabidopsis lines. Taken together, it suggested that CsPUPs were involved in caffeine transport in tea plants. Potential roles of CsPUPs in the intracellular transport of caffeine among different subcellular organelles were proposed. This study provides a theoretical basis for further research on the PUP genes and new insights for caffeine metabolism in tea plants.